1993
DOI: 10.1021/es00044a021
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fuel structure on emissions from a spark-ignited engine. 3. Olefinic fuels

Abstract: A single-cylinder, production-type engine has been run at four operating conditions on four olefinic fuels (ethylene, 1-butene, 1-hexene, and diisobutylene) and two blends (n-hexane with toluene and 20 % diisobutylene with a fully blended gasoline). Engine-out hydrocarbon (HC) emissions (total and species), NO*, CO, and CO2 have been measured. Total HC emissions from the olefinic fuels increase with the molecular weight of the fuel (e.g., from 320 ppm Cj for ethylene to 1420 ppm Ci for diisobutylene during lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
23
0

Year Published

1994
1994
2007
2007

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(26 citation statements)
references
References 6 publications
3
23
0
Order By: Relevance
“…These results are certainly very interesting. However, the observations and conclusions drawn in their paper are in large measure identical (with certain exceptions) to those presented earlier in a series of publications from the Ford Motor Co., [2][3][4][5][6] which have not been cited by the authors. For this reason, I believe it is important to discuss briefly the Ford results and to compare them to this Journal paper.…”
supporting
confidence: 78%
See 1 more Smart Citation
“…These results are certainly very interesting. However, the observations and conclusions drawn in their paper are in large measure identical (with certain exceptions) to those presented earlier in a series of publications from the Ford Motor Co., [2][3][4][5][6] which have not been cited by the authors. For this reason, I believe it is important to discuss briefly the Ford results and to compare them to this Journal paper.…”
supporting
confidence: 78%
“…In addition, the abstract reports that "the aromatic blend (containing xylenes and ethylbenzene) produces significant quantities of both benzene (2-5%) and toluene (3-6%) in the engine-out emissions." (3) The abstract of Kaiser et al 1993 4 states, "1,3-butadiene (emission) is significant for the straight-chain terminal olefin (fuels), 1-butene and 1-hexene, but is much less important for the highly-branched olefin diisobutylene." (4) Although not discussed specifically in Kaiser and Siegl 1994, 5 Table 1 in that article shows that methacrolein is present in the engine-out exhaust from pure isooctane fuel at a level approximately 3-4 times larger than from the gasoline fuel in Table 3, which contains 11% isooctane.…”
mentioning
confidence: 99%
“…Therefore, the results obtained in this study should not be adopted directly for policy decisions in other countries. Moreover, recent studies have indicated the PAH emissions from the gasoline-powered engine might also be affected by the types of lubricant (15) and catalytic converter (16). Because other types of engine, gasoline fuel, lubricant, and catalytic converter will affect PAHs emission in the engine exhaust, further studies should be conducted to extend the generality of the above findings.…”
Section: Yearmentioning
confidence: 89%
“…Benzene, toluene, C2-benzenes and C3-benzenes are the major fuel precursors for benzene emissions. Recent work in our laboratory suggests that the combustion of cyclohexane, methylcyclohexane and terminal olefins leads to relatively high levels of 1,3-butadiene (26,35). Further studies using the PFC and single-cylinder engine are needed to determine the importance of other fuel species for the formation of 1,3-butadiene.…”
Section: Discussionmentioning
confidence: 99%